SPATIAL AND SECTORAL PRODUCTIVITY CONVERGENCE BETWEEN EUROPEAN REGIONS, 1975-2000 - Julie Le Gallo; Sandy Dall'erba (European Regional Science Association (ERSA), 2005)
This paper analyzes the evolution of labor productivity disparities among 145 European regions over 1975-2000 according to the concepts of sigma- and beta-convergence and emphasizes the importance of including both spatial effects and a disaggregated analysis at a sectoral level. We detect sigma-convergence in aggregate labor productivity and in the service sectors but not in the other sectors. This result can be explained by a transfer of resources from the agricultural sector to the more productive sectors that has been more marked in the poor regions. Empirical results also indicate that the common indicator of sigma-convergence lead to a bias when spatial effects are not included in the analysis. We then estimate beta-convergence models including the relevant spatial effects for each sector. The results show that inequality in productivity levels between core and peripheral regions persist and highlight how convergence speeds and the nature of spatial effects vary from one sector to another.
Keywords: 330